Estimating Greenhouse Gas Emissions from Household Activities: A Case in Bogor Indonesia - Al Zahroh, Dina Naba; Hidayat, Aceng; Irfany, Mohammad Iqbal (SMART Insight, 2024)
Climate change is a result of global warming. Global warming is caused by an increase in the concentration of greenhouse gases (GHGs) in the atmosphere. One of the largest GHG-contributing sectors is the energy sector, which includes households with various activities. Household activities include using LPG, electricity, gasoline, waste generation, and farming and livestock activities to meet the household's needs. The level of GHG emissions produced in households is influenced by income, years of study, and knowledge of emissions. The objectives of this study are to estimate the amount of GHG emissions generated from household activities, analyze the factors that influence GHG emissions, and estimate the value of the carbon economy. The analytical methods used are quantitative descriptive analysis, IPCC (2006) method, multiple linear regression, and economic value analysis. The results showed that: (1) CO2-eq emissions generated in Sinarsari Village for 100 respondents amounted to 32,011.68 kg CO2-eq/month, and the amount of GHG emissions in one village scope amounted to 853,431.36 kg CO2-eq/month. (2) Income, length of study, and emission knowledge dummy influence GHG emissions. 3) Carbon economic value based on carbon pricing is Rp287,415,199.70/month.